Translation of Conceptual Metaphor of Fear in English into Indonesian and Turkish: A Comparative Study - Hyunisa Rahmanadia; Siti Sa’diah (PRASASTI: Journal of Linguistics, 2024)
In cognitive linguistics, conceptual metaphor is known to reflect the human’s thinking process. Thus, the translation of the conceptual metaphor itself is challenging due to its cultural-bounded lexical. This research compares the conceptual metaphor of fear in an English text and the translation in Indonesian and Turkish. The aim of the research is to show how a conceptual metaphor of fear in English is transferred to Indonesian and Turkish translation. The data was taken from an international bestseller novel, ‘The Kite Runner’, written by Khaled Hosseini, and the translation in Indonesian and Turkish. The equivalent word of fear that the writer used to find the conceptual metaphor is ketakutan in Indonesian and korku in Turkish. This paper is qualitative driven research conducting in-depth analysis from the data collected. As a result, seven conceptual metaphors of fear are found in the source text, namely FEAR IS SOUND, FEAR IS A VISIBLE OBJECT, FEAR IS HIDDEN ENEMY, FEAR IS PAIN, FEAR IS SUBSTANCE, FEAR IS BURDEN, and FEAR IS TASTE. In translation, it is revealed that some of the conceptual metaphors are translated faithfully for both languages, and some have undergone reconstruction to meet the target language criteria. This result shows that universal metaphor is applied in the languages, proving that the same metaphor can be transferred in the target languages. Moreover, this paper also shows that these three languages see the emotional concept of fear in a different way of thinking.